ANALYZING THE IMPACT: EMERGING CLASSROOM TECHNOLOGIES AND THE EVIDENCE ON LEARNING - Azlinda Zainal Abidin; Putriyani, Della Widya; Djoko Sutrisno (Global Synthesis in Education Journal, 2023)
This paper aimed to analyze the multifaceted impact of modern technological integration in education on pedagogy, learning processes and outcomes. A detailed literature review was conducted examining key developments in educational technologies over the past two decades including online learning platforms, 1:1 device initiative, and adaptive learning software. Impacts were analyzed using existing evidence from multiple systematic reviews and meta-analyses on learning analytics, engagement, student achievement and teaching practices. The integration of technology in classrooms was found to enable more self-directed, personalized learning approaches leading to significant gains in core skills. However, uneven access to technology and issues around data privacy were also highlighted. Benefits were maximized when technologies supplemented rather than substituted teachers. With astute policy and teacher training, classroom technology presents transformative opportunities to improve access, equity, achievement and prepare students with vital future-oriented skills. However, care must be taken to continually address ethical issues around privacy, screen time, and digital divides. Understanding both opportunities and pitfalls will be key as education systems leverage technologies effectively to enhance learning on a global scale in coming decades